E Marketing Strategies of Micro, Small, and Medium Enterprises (MSMEs) in Increasing Sales Through Marketplaces: An Islamic Economics Perspective - Nailin Nikmatul Maulidiyah; Wahid Syafruddin; Syed Iradat Abbas; Imam Asrofi; Eny Widiaty; Baiq Ismiati (Institute Agama Islam Tafaqquh Fiddin Dumai, 2025)
This study aims to analyze the marketing strategies of Micro, Small, and Medium Enterprises in enhancing sales through marketplaces from the perspective of Islamic economics. The marketplace was chosen due to its significant role in expanding market reach, strengthening competitiveness, and building consumer trust in the digital era. The research employed a qualitative descriptive method with a netnographic approach, focusing on the observation of Micro, Small, and Medium marketing practices on Shopee and Tokopedia. Data were collected through the examination of product catalogs, promotional activities, seller buyer interactions, and digital documentation. The findings indicate that the main strategies implemented include catalog optimization, the use of promotional features, active consumer engagement, paid advertising, and collaboration with digital influencers. These strategies proved effective, with sales increasing by 25% through catalog optimization, transactions rising by 40% during promotional periods, and sales conversion improving by 30% through advertising. From the perspective of Islamic economics, these practices reflect the principles of shidq (truthfulness), taysir (facilitation), ihsan (excellence), and amanah (trustworthiness). Moreover, they represent the actualization of maqashid al-shariah, particularly in preserving wealth (hifdz al-maal), life (hifdz al-nafs), morality (hifdz al-akhlaq), and honor (hifdz al-‘irdh).